Neonatal sepsis is associated with behavioral abnormalities in very low birthweight infants at preschool age - Giordano, Vito; Stummer, Sophie; Lindtner, Claudia; Fuiko, Renate; Berger, Angelika; Pichler, Karin (Frontiers in Pediatrics, 2022)
Objective This study aimed to investigate neonatal sepsis as potential risk factor for adverse behavioral outcome in very low birth weight infants (VLBWI) at preschool age. Regardless of improvements in the obstetric and neonatal intensive care, preterm infants are still at high risk for behavioral problems later in life. The spectrum, origin and potential risk factors of these behavioral problems have not been well defined. Methods In this retrospective observational study the influence of culture-proven neonatal sepsis on the behavioral outcome of VLBWI born at a gestational age < 32 weeks was analyzed at 5 years of age in a multivariable regression model. Behavior was assessed with the Child Behavior Checklist (CBCL). Neonatal morbidities, socioeconomic status and neurodevelopmental outcome served as covariates in the analysis. Results 312 VLBWI entered the final analysis, of whom 11% had experienced neonatal sepsis. Neonatal sepsis appeared to be a relevant risk factor for both internalizing, i.e. emotional reactivity and anxiety/depression, as well as externalizing behavioral problems, i.e, oppositional and aggressive behavior in this cohort of VLBWI. Low socioeconomic status and male gender were additional statistically significant risk factors for both internalizing and externalizing behavioral problems. No difference in neurocognitive development was observed between the groups. Conclusion The study supports the fact that VLBWI are vulnerable to multiple behavioral disorders independent of their cognitive development. In contrast to former assumptions, the results of the study emphasize that not only postnatal environment but also neonatal morbidities, especially neonatal sepsis, have an impact on behavioral outcome of VLBWI at preschool age.